Pentingnya Penerapan Good Corporate Governance Terhadap Pengelolaan UMKM Menurut Sudut Pandang Bisnis Syariah Islam - Pangesti, Atisa; Khotimah, Chusnul; Djasuli, Mohamad (CV. ITTC INDONESIA, 2022)
The author analyzes government policies for developing the economic interests of citizens to support MSMEs (small and medium enterprises) using the principles of good governance. This research uses a qualitative descriptive study of the type of literature through the use of secondary data sources. The results of research on several steps of public regulation using good governance management that need to be implemented are: 1). Socialization program and strategic outreach, 2). Describing HR (human resources) and having adequacy, 3). Entrepreneurial spirit created for small and medium society 4). There are business consumers (market segmentation) and monitoring and continuous improvement (Quality Improvement).